Praktik Sosial Remarriage pada Masyarakat Minangkabau di Kenagarian Padang Ganting - Desmaisi Desmaisi; Jendrius Jendrius; Maihasni Maihasni (Jurnal Sosiologi Andalas, 2023)
: Remarriage is an individual who is married the same or more than twice by a man or a woman. Usually, marriage is done once in a lifetime. However, in Nagari Padang Ganting found men and women married many times. This study uses a qualitative method. Data was collected using in-depth interviews, observation and secondary data analysis. The practice of social remarriage (marriage again) in the Minangkabau community in Kenagarian Padang Ganting studied with structuration theory by Anthony Giddens is known that there are structures that enable or empower "remarriage" itself. But there are also structures that constrain or curb “remarriage”. Of the two divisions, the empowering structure tends to be more dominant than the restraining structure. Men don't have space in their parents' homes, there are parties looking for a mate, the value of children as continuation of offspring, male providers, stigmatization of widows and two, men remarry to take care of their needs, second and subsequent marriages are easier to do and the practice of remarriage is a common thing to do into a structure that perpetuates remarriage. Meanwhile, remarriage is considered to increase men's economic responsibilities, the marriage law makes it difficult for divorce to occur and women carry out the parenting role posterity becomes a structure that restrains perpetrators frim remarriage.